Rapid clearance of Giardia lamblia DNA from the gut after successful treatment. (November 2014) - van den Bijllaardt, W.; Overdevest, I. T.; Buiting, A. G.; Verweij, J. J.; Bottieau, E.
Abstract To assess the time it takes for a real‐time PCR to become negative after treatment of a Giardia lamblia infection, we evaluated two consecutive follow‐up samples from 75 infected patients. Approximately 1 week after treatment all samples tested negative, indicating rapid clearance of parasitic DNA after successful treatment.